AN ACCELERATED METHOD OF DIPHTHERIA GENE DIAGNOSTICS BASED ON ISOTHERMAL AMPLIFICATION TO DETECT DNA OF THE CAUSATIVE AGENT - O. Yu. Borisova (Журнал микробиологии, эпидемиологии и иммунобиологии, 2017)
Aim. Development of an accelerated method of gene diagnostics of diphtheria based on isothermal amplification for detection of DNA of the causative agent. Materials and methods. The study was carried out in typical collection strains from GKPM-Obolensk, as well as in 135 strains of C. diphtheriae isolated from bacteriological laboratories of the regions of Russian Federation and sent to the Gabrichevsky Moscow Research Institute of Epidemiology and Microbiology Strain isolation was carried out in accordance with Ml 4.2.698-98 and 4.2.3065-13. Chromosomal DNA was isolated by standard heating method, as well as using 3 commercial kits. Detection of the amplification results was carried out in horizontal electrophoresis in 1.5% agarose gel. Results. The developed method of gene diagnostics was established to allow detection of DNA of toxigenic C. diphtheriae strains of 2 biovars, as well as DNA of non-toxigenic tox-gene bearing strains (NTTB) of C. diphtheriae mitis biovar with mechanisms of lack of expression of diphtheria toxin gene due to the presence of deletion or mobile genetic IS element in the tox gene. Non-toxigenic tox-gene bearing C. diphtheriae strain with the mechanism of lack of diphtheria toxin gene expression due to the presence of transposon in the tox gene are identified as non-toxigenic. Evaluation of the analytical sensitivity in comparative studies using 3 commercial kits for FNA isolation has shown that sensitivity reached 4.5x 101 GE/ml using Ribo-prep kit. H igh specificity of the developed method is shown, it was evaluated in 18 strains of 16 other members of the Corynebacterium genus and 20 typical strains of microorganisms isolated from oropharynx or causing infections of the respiratory tract. Approbation of the developed method was carried out in model experiments in imitators of clinical samples by infection of single-use sterile dry tampons by consecutive dilutions of the bacterial cultures (with parallel seeding into dense nutrient media) and was 103 GE/ml. Conclusion. The developed method of accelerated gene diagnostics of the diphtheria infection has a high diagnostic effectiveness, specificity and sensitivity, allows to detect 103 - 4.5x10 GE/ml C. diphtheriae in clinical material with simultaneous verification of toxigenic and non-toxigenic strains.